2017
DOI: 10.1002/cncy.21839
|View full text |Cite
|
Sign up to set email alerts
|

Cytological, molecular, and clinical features of noninvasive follicular thyroid neoplasm with papillary‐like nuclear features versus invasive forms of follicular variant of papillary thyroid carcinoma

Abstract: BACKGROUND:The noninvasive follicular variant of papillary thyroid carcinoma (PTC) has an indolent clinical behavior in comparison with other PTCs, including the invasive follicular variant of papillary thyroid carcinoma (IFVPTC). Recently, the term noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) was introduced to emphasize the low biological potential of these tumors. This study compares clinical, cytological, and molecular features of NIFTP and IFVPTC. METHODS: The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
112
1
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 33 publications
5
112
1
1
Order By: Relevance
“…They concluded that because of the overlapping nuclear features with invasive EFVPTC, NIFTP cannot be reliably diagnosed preoperatively 14. Similarly, Zhao et al15 believe that even though there are differences in the cytological and molecular profiles between NIFTP and infiltrative follicular varient of papillary carcinoma (IFVPTC), the overlap between the two makes it implausible to correctly differentiate between NIFTP and IFVPTC in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that because of the overlapping nuclear features with invasive EFVPTC, NIFTP cannot be reliably diagnosed preoperatively 14. Similarly, Zhao et al15 believe that even though there are differences in the cytological and molecular profiles between NIFTP and infiltrative follicular varient of papillary carcinoma (IFVPTC), the overlap between the two makes it implausible to correctly differentiate between NIFTP and IFVPTC in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…Our literature review revealed variable results between studies. NIFTP cases diagnosed as category VI vary between 0 and 18% [14]. Maletta et al [7] diagnosed NIFTP as Bethesda category IV in 56% of cases, V in 27%, III in 15%, and VI in 2%.…”
Section: Discussionmentioning
confidence: 99%
“…Mainthia et al [4] classified NIFTP as Bethesda category III in 26%, IV in 20%, V in 9%, II in 18%, I in 11%, and VI in 6%. Zhao et al [14] classified 72% of NIFTP cases as Bethesda category III. Strickland et al [15] diagnosed NIFTP mainly as Bethesda categories V (45.8%), III (20%), and II (15.2%).…”
Section: Discussionmentioning
confidence: 99%
“…1 Recently, the Endocrine Pathology Society working group conducted a retrospective study of noninvasive encapsulated FVPTC with the aim of assessing clinical outcomes, refining diagnostic criteria, and developing a new terminology that appropriately reflects the biological and clinical characteristics of this entity. The rate of histology-proven malignancy after implementation of TBSRTC was 3.5%, 17 2 The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) has been widely accepted as a standard reporting system for assessing fine needle aspiration (FNA) of thyroid.…”
Section: Introductionmentioning
confidence: 99%